3,4-Dihydroxybenzaldehyde 4-phenylthiosemicarbazone - Tan, Kong Wai (International Union of Crystallography, 2008)
Molecules of the title compound, C(14)H(13)N(3)O(2)S, are linked by intermolecular O—H⋯O hydrogen bonds into centrosymmetric dimers forming R (2) (2)(4) rings which are further linked by O—H⋯S hydrogen bonds and weaker N—H⋯S and N—H⋯O hydrogen bonds to form a three-dimensional network.